Incidencia financiera de la aplicación de un planeamiento tributario en las empresas comerciales de la ciudad de trujillo - Mundaca Gonzales, Gladis (2011)
The purpose of the research was to determine the financial impact of implementing a Business Tax Planning in the Commercial City of Trujillo Currently, the tax administration, in relation to their tax debt collection is growing fast, demanding the payment of taxes regardless of external factors affecting the economy of companies such as the recent economic crisis. The research question was: What is the financial impact of implementing a Business Tax Planning in the Commercial City of Trujillo?. The hypothesis raised was this: The Application of Tax Planning adequate positive impact on the financial management of commercial enterprises in the city of Trujillo. According to the results it is recommended that businesses in the city of Trujillo will continue to use tax planning for the positive impact, and be considered a tool that has the taxpayer to legally minimize or reduce the effects on the cost of taxes you pay. It is hoped that this study will serve as a benchmark for private information to the institutions of the City of Trujillo, when making their choices between tax planning.